A comparative study of thumb reconstruction through the transplant of the first toe compound free flap between emergency surgery and elective surgery. Issue 34 (26th August 2022) - Ge, Lei; Liu, Qiandong; Wang, Xiangyun; He, Qiang; Zhang, Lei; Lu, Libin; Dong, Qinglin; Gao, Yang
Abstract : This study compared emergency surgery with elective surgery for thumb reconstruction to explore the advantages, safety, and clinical value of emergency reconstruction. By comparing the advantages and disadvantages of thumb reconstruction in emergency surgery and elective surgery, it provides data support for optimizing the treatment process and methods. In this study, 22 patients who underwent thumb reconstruction in Rizhao people's Hospital from January 2018 to December 2020 were randomly divided into emergency operation group and elective operation group. The differences in operation period, hospitalization time, postoperative complications, hand function score, and satisfaction score between the 2 groups were analyzed. The operation period and hospitalization time of patients in the emergency surgery group were significantly lower than those in the elective surgery group, with statistical significance ( P < .05). There was no significant difference in postoperative complications between the 2 groups ( P > .05). After 3 months of rehabilitation training, the 2-point discrimination, functional score, and satisfaction score of the reconstructed thumb in the emergency surgery group were higher than those in the elective surgery group, and the difference was statistically significant ( P < .05). Emergency reconstruction of the thumb can reduce operation time and hospitalization time, reduce operation costs, and obtain a more ideal appearance and function.